Ceratitis capitata genetic sexing strains: laboratory evaluation of strains from mass‐rearing facilities worldwide. Issue 3 (20th October 2017) - Augustinos, A.A.; Targovska, A.; Cancio‐Martinez, E.; Schorn, E.; Franz, G.; Cáceres, C.; Zacharopoulou, A.; Bourtzis, K.
Abstract: The Mediterranean fruit fly, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), is among the most destructive and cosmopolitan species of the family. It has been studied extensively and has become a model species for sterile insect technique (SIT) applications. More than 3 decades of coordinated research led to the development and continuous improvement of genetic sexing strains (GSSs) for this pest. The last generation of these strains (Vienna 7 and Vienna 8), developed at the FAO/IAEA Insect Pest Control Laboratory (IPCL) in Seibersdorf, Austria, presents a combination of characters that calls for specialized control and evaluation methods, especially in mass‐rearing conditions. In this paper, we present the results of two small‐scale laboratory tests that can evaluate the stability, productivity, and other properties of these strains and have been used in IPCL since their development. These tests were used for the analysis of the Vienna 7 and Vienna 8 GSSs after their re‐introduction to the IPCL from the different rearing facilities. Our data show the robustness and stability of the 'sexing' character of these strains but also point to differences among them regarding egg hatch, pupation, adult emergence rates, and male tolerance to elevated temperatures. Well‐defined, small‐scale protocols allow the continuous monitoring of the properties of putative important strains; they can be used as standard operating protocols to enable unbiased comparison among strains available in different mass‐rearing facilities.